Cognition, structural brain changes and complicated grief. A population-based study. Issue 7 (3rd November 2014) - Saavedra Pérez, H. C.; Ikram, M. A.; Direk, N.; Prigerson, H. G.; Freak-Poli, R.; Verhaaren, B. F. J.; Hofman, A.; Vernooij, M.; Tiemeier, H.
Abstract : Background: Several psychosocial risk factors for complicated grief have been described. However, the association of complicated grief with cognitive and biological risk factors is unclear. The present study examined whether complicated grief and normal grief are related to cognitive performance or structural brain volumes in a large population-based study. Method: The present research comprised cross-sectional analyses embedded in the Rotterdam Study. The study included 5501 non-demented persons. Participants were classified as experiencing no grief ( n = 4731), normal grief ( n = 615) or complicated grief ( n = 155) as assessed with the Inventory of Complicated Grief. All persons underwent cognitive testing (Mini-Mental State Examination, Letter–Digit Substitution Test, Stroop Test, Word Fluency Task, word learning test – immediate and delayed recall), and magnetic resonance imaging to measure general brain parameters (white matter, gray matter), and white matter lesions. Total brain volume was defined as the sum of gray matter plus normal white matter and white matter lesion volume. Persons with depressive disorders were excluded and analyses were adjusted for depressive symptoms. Results: Compared with no-grief participants, participants with complicated grief had lower scores for the Letter–Digit Substitution Test [ Z -score −0.16 v. 0.04, 95% confidence interval (CI) −0.36 to −0.04, p = 0.01] and Word Fluency Task ( Z -score −0.15 v. 0.03, 95% CI −0.35 to −0.02, p = 0.02) and smaller total volumes of brain matter (933.53 ml v. 952.42 ml, 95% CI −37.6 to −0.10, p = 0.04). Conclusions: Participants with complicated grief performed poorly in cognitive tests and had a smaller total brain volume. Although the effect sizes were small, these findings suggest that there may be a neurological correlate of complicated grief, but not of normal grief, in the general population.